A Study on Teaching Chinese Second Language Interjection Based on PACE Teaching Model: 基于PACE教学模式的汉语二语叹词教学研究 - Lishen, Yu; Qingqing, Kong (Mandarinable: Journal of Chinese Studies, 2000)
The PACE teaching model combines the advantages of teaching a second language explicit grammar and implicit grammar. The PACE teaching model is introduced comprehensively, and the Chinese interjection"啊、唉、嗯、呦、哎呀、哦、嘛、呢" are selected and studied in the design of teaching Chinese second language interjection based on the PACE model. Finally, the applicability of the PACE teaching model to the teaching of Chinese second language interjection is analyzed from the perspectives of the advantages of the PACE teaching model, the difficulty of acquiring interjection and the characteristics of the textbook layout, which provides Chinese teachers with new ideas for teaching Chinese grammar.